A Cultural History of Chemistry in Antiquity - Beretta, Marco (The Cultural Histories Series, 2021)
This open access bookA Cultural History of Chemistry in Antiquity covers the period from 3000 BCE to 600 CE, ranging across the civilizations of the Mediterranean and Near East. Over this long period, chemical artisans, recipes, and ideas were exchanged between Mesopotamia, Egypt, Phoenicia, Greece, Rome, and Byzantium. The flowering of alchemy in the Middle and Early Modern Ages had its roots in the chemical arts of antiquity. This study presents the first synthesis of this epoch, examining the centrality of intense exchange and interconnectivity to the discovery and development of sources, techniques, materials, and instruments. The 6 volume set of the Cultural History of Chemistry presents the first comprehensive history from the Bronze Age to today, covering all forms and aspects of chemistry and its ever-changing social context. The themes covered in each volume are theory and concepts; practice and experiment; laboratories and technology; culture and science; society and environment; trade and industry; learning and institutions; art and representation. Marco Beretta is Professor of History of Science at the University of Bologna, Italy. Volume 1 in the Cultural History of Chemistry set. General Editors: Peter J. T. Morris, University College London, UK, and Alan Rocke, Case Western Reserve University, USA. The open access edition of this book is available under a CC BY-NC-ND 4.0 license on www.bloomsburycollections.com. Open access was funded by the European Research Council.